Liver transplantation for alcohol-related liver disease in the UK: revised UK Liver Advisory Group recommendations for referral. (November 2021) - Masson, Steven; Aldersley, Helen; Leithead, Joanna A; Day, Ed; Langford, Andrew; Healy, Pamela; O'Grady, John; Thorburn, Douglas; Parker, Charlotte; Shepherd, Liz; Arndtz, Katherine; Webb, Kerry; et al.
Summary: Liver disease, of which liver cirrhosis is the most advanced stage, constitutes the fourth most common cause of life-years lost in men and women younger than 75 years in England, where mortality rates from liver disease have increased by 25% in the past decade. Alcohol consumption is the most common modifiable risk factor for disease progression in these individuals, but within the UK, there is substantial variation in the distribution, prevalence, and outcome of alcohol-related liver disease, and no equity of access to tertiary transplantation services. These revised recommendations were agreed by an expert panel convened by the UK Liver Advisory Group, with the purpose of providing consensus on referral for transplant assessment in patients with alcohol-related disease, and clarifying the terminology and definitions of alcohol use in liver injury. By standardising clinical management in these patients, it is hoped that there will be an improvement in the quality of care and better access to liver transplant assessment for patients with alcohol-related liver disease in the UK.